(untitled) (Development Service Industry Management, 2025)
The article examines the current state of development of the hotel and restaurant sector in the Zakarpattia region, which is determined by the region’s natural and recreational potential and the activation of domestic and inbound tourism. Quantitative parameters of market functioning, reflecting structural changes and development trends over recent years, have been established. It has been clarified that the reduction in the number of collective accommodation facilities in Ukraine is accompanied by a relative stabilization of indicators in Zakarpattia, indicating an increased role of the region in the national market. Emphasis is placed on the significance of the financial aspect of hotel and restaurant operations, which determines the economic activity of local communities and the formation of local budgets. The importance of analyzing tax revenues as a tool for evaluating the effectiveness of managerial decisions and the investment attractiveness of territories is highlighted. A high level of territorial differentiation of income and the dependence of the service market on transport accessibility, tourist attractiveness, and infrastructure have been noted. Key factors influencing the quality of hotel and restaurant services have been identified. Practical aspects of service management are considered through the example of leading hotel and restaurant complexes in Zakarpattia, such as “Kilikia”, “Duet Plus”, PIKUY and “Synevyrskyi Pereval”. The effectiveness of an integrated approach to service organization, combining comfort, gastronomic services, recreation, and digital customer interaction tools, has been established. The role of cultural and identity elements in forming a unique “regional service brand” has been clarified. It is emphasized that the systematic integration of standards, technologies, and local traditions contributes to enhancing the region’s competitiveness and forming a sustainable positive image of Zakarpattia. The significance of developing partnership networks and environmentally oriented practices in hospitality is underlined. It is noted that the digitalization of service processes ensures operational efficiency, transparency, and controllability of service delivery.